Instructional Analysis In Speaking Classroom - Nurhasanah; Wiwid Eka Agustin; Merie Agustiani (Edukasi Lingua Sastra, 2020)
The objective of the research is to know the instructional analysis in teaching speaking skill. This study participated by one of the Eleventh grader English teachers in SMAN 8 OKU. Data from this descriptive study were gathered by observation. The observational result showed that the English teacher of SMA N 8 OKU used certain types of classroom instruction in the teaching speaking. There were five types of classroom instruction: setting objectives and providing feedback, cues, question and advanced organizer, homework and practice, reinforcing effort and providing recognition, and generating and testing hypotheses